Beyond Administrative Formalities: Village Fund Oversight, Corruption, and Social Accountability in Bima Regency - Mukhlis Ishaka; Rahmad Hidayat (Indonesian Journal Publisher, 2025)
Existing studies on village governance and public accountability have largely focused on institutional and structural drivers of corruption, often overlooking the interplay between administrative practices, local power dynamics, and perpetrator motivations. Accountability failures are shaped by these interactions as much as by formal structures. This study examines village fund oversight in Mawu and Waduruka Villages, Bima Regency, Indonesia. Using a qualitative case study, the authors collected data through field observations, document analysis, and in-depth interviews with village officials, members of the Village Consultative Body (BPD), community representatives, government auditors, village facilitators, and corruption perpetrators. Key findings include: (1) Oversight is predominantly focused on procedures and compliance with regulations, which allows genuine accountability to be hidden; (2) Administrative approaches, along with limited ability of institutions to perform their functions, minimal resources for financial review (auditing), and deeply rooted relationships between patrons (people in power) and clients (dependent supporters), directly lead to fake documents, inflated budgets, and fictional activities; (3) Citizen participation is disjointed and mainly reactive, occurring after corruption comes to light; (4) The idea of the 'administrative formality trap'—where official systems for accountability exist but meaningful evaluation or enforcement is missing—shows that such systems can unintentionally allow corruption. These findings together offer a more complete